2019
DOI: 10.1590/1980-5373-mr-2018-0401
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologically-Influenced Corrosion of 1020 Carbon Steel in Artificial Seawater Using Garlic Oil as Natural Biocide

Abstract: This work aims evaluate the use of biocides in the microbiologically-influenced corrosion (MIC) of AISI 1020 carbon steel by sulfate-reducing bacteria (SRB) in artificial seawater. A natural biocide (garlic oil) and a commercial biocide (glutaraldehyde) were used to control the corrosion caused by these bacteria in artificial seawater. Microbial growth on the steel surface was evaluated by quantifying the sessile SRB using the most probable number (MPN) method. The action of biocides in the biocorrosion proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…They can destroy the cell membrane of SRP, cause cell death, and destroy the formation of biofilm [ 126 ]. Silva et al [ 127 ] compared the performance of garlic oil and glutaraldehyde as biocides to prevent MIC. The results showed that both garlic oil and glutaraldehyde can reduce the corrosion of steel and prevent the formation of biofilm.…”
Section: Biocidesmentioning
confidence: 99%
“…They can destroy the cell membrane of SRP, cause cell death, and destroy the formation of biofilm [ 126 ]. Silva et al [ 127 ] compared the performance of garlic oil and glutaraldehyde as biocides to prevent MIC. The results showed that both garlic oil and glutaraldehyde can reduce the corrosion of steel and prevent the formation of biofilm.…”
Section: Biocidesmentioning
confidence: 99%
“…Cinnamaldehyde immobilized onto MSNPs proved to be the most effective antimicrobial from the tested EOs, with the potential to be used to treat and prevent bacterial infections in crops and to enable more controlled and effective exploitation of volatile compounds as antimicrobials. 17 In addition, EOs can have many applications as food preservatives, [18][19][20] corrosion inhibitors, 21 preservation of cultural heritage, 22 etc. Different materials have been used to encapsulate EOs, including polymeric particles, liposomes, and solid lipid NPs, and a detailed review of EO encapsulation can be found in the literature.…”
Section: The Use Of Natural Compounds As Biocidesmentioning
confidence: 99%
“…Te limit for chemical biocides is that they are toxic and ecologically unfriendly [18]. Recently, researchers have developed an ecofriendly biocide to address this issue [19][20][21].…”
Section: Introductionmentioning
confidence: 99%